Hydrothermal Synthesis and Photocatalytic Activity of NiO Nanoparticles under Visible Light Illumination - J. Anita Lett; Suresh Sagadevan; Getu Kassegn Weldegebrieal; Is Fatimah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this present study, Nickel oxide (NiO) nanoparticles (NPs) have been synthesized using the hydrothermal method and characterized using powder X-ray Diffraction (XRD), UV-vis and Fourier Transform Infra Red (FTIR) spectroscopies, Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray (EDX) methods. The result of the characterization indicates that the synthesized sample has a pure cubic phase of NiO with roughly spherical shape morphologies and respective estimated crystallinity and microstrain values of about 78% and 5.1. Test of the photocatalytic activity of the synthesized sample towards the model contaminant dye methylene blue (MB) shows a degradation efficiency of 46% in a period of 2 h under nature sunlight irradiation at natural pH and that the reaction could satisfactorily describe both pseudo-first-order and pseudo-second-order kinetic models. So, this synthesis method may potentially be used for the effective elimination of toxic organic pollutants from water and wastewater over prolonged exposure under natural sunlight without adding any oxidant or adjusting the pH of the reaction medium. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).